Synthesis of carboxyl group functionalized silica composite resin for strontium removal. (5th January 2020) - Wang, Siyi; Ning, Shunyan; Zhang, Wei; Zhang, Shichang; Zhou, Jie; Wang, Xinpeng; Wei, Yuezhou
Abstract: Radioactive strontium 90 Sr with a half-life of 29 years is one of the most concerned elements in both nuclear accidents and spent fuel reprocessing. Herein, using macroporous silica SiO2 as support, methylacrylic acid as functional monomer and ethylene glycol dimethacrylate as cross-linking agent, a novel resin named SiMaC was prepared via in situ polymerization method for strontium removal. The as-preapred SiMaC was characterized by SEM-EDS, TG-DSC, and BET. Various factors such as pH, m/V, time, and initial concentration of Sr(II) were studied. The maximum adsorption capacity towards Sr(II) was as high as 142.5 mg/g at 298 K. The adsorption equilibrium was almost obtained within 30 min. Moreover, SiMaC was easily and fastly regenerated by 0.1 M HCl and exhibited no obvious decrease in adsorption capacity after five times of successive adsorption-desorption cycles. Most attractively, the uptake rate of Sr(II) reached more than 99% in real river and lake water mediums, as well as reached 76% in real seawater mediums. Finally, XPS and FTIR were used to analyze the adsorption mechanism towards Sr(II). Graphical abstract: Image 1 Highlights: A carboxyl functionalized resin SiMaC was prepared via in situ polymerization. The adsorption isotherm, kinetics, and thermodynamics of Sr on SiMaC were explored. SiMaC exhibited a maximum adsorption capacity of 142.5 mg/g towards Sr(II). The uptake rate of Sr in river water, lake water and sea water are 99%, 99% and 76%. SiMaC is a promsing resin for Sr adsorption and recovery.